PENGARUH PEMBIAYAAN MURABAHAH, BIAYA OPERASIONAL DAN â€œCOST OF CREDITâ€ TERHADAP LABA PADA PT BANK MEGA SYARIAH AREA SULAWESI - Sastrawan, Erwan (Katalogis, 2015)
This study aims to: 1). Seek and analyze simultaneous influnce of murabahah financing operational cost, and cost of credits on profit at PT. Mega Syariah Bank Sulawesi Area; 2). Seek and analyze partial influnce of murabahah financing, oparational cost, and cost of credit on profits at PT. Mega Syariah Bank Sulawesi area. The study is conducted in 20 KC and KCP offices in Sulawesi Area by focusing on their financial report in 3 years. The result of multiple linear regressions indicates that: 1). Murabahah finance, oparational cost, cost of credit simultanneously influence the profit gained by PT. Mega Syariah bank Sulawesi Area; 2). Murabahah finance positively and significantly influence the profit of PT. Mega Syariah Bank Sulawesi Area; 3). Operational cost negatively and significantly influence the profit of PT. Mega Syariah Bank Sulawesi Area; 4). Cost Of credit negatively and significantly influence the profit of PT. Mega Syariah Bank Sulawesi Area.